Neutron microtomography-based virtual extraction and analysis of a cercopithecoid partial cranium (STS 1039) embedded in a breccia fragment from sterkfontein member 4 (South Africa) - (:unkn) unknown (My University, 2016)
The Plio-Pleistocene karstic sedimentary deposits of Sterkfontein Cave, South Africa, yielded numerous fossil primate specimens embedded in blocks of indurated breccia, including the partial cercopithecoid cranium labelled STS 1039. Because the surrounding matrix masks most of its morphology, the specimen remains taxonomically undetermined. While the use of X-ray microtomography did not allow extracting any structural information about the specimen, we experimented a new investigative technique based on neutron microtomography. Using this innovative approach, we successfully virtually extracted, reconstructed in 3D and quantitatively assessed the preserved dentognathic structural morphology of STS 1039, including details of its postcanine maxillary dentition. Following comparative analyses with a number of Plio-Pleistocene and extant cercopithecoid taxa, we tentatively propose a taxonomic attribution to the taxon Cercopithecoides williamsi. Our experience highlights the remarkable potential of this novel imaging method to extract diagnostic information and to identify the fossil remains embedded in hard breccia from the South African hominin-bearing cave sites.
Keywords: African Research